Type 1 versus type 2 fuzzy logic speed controllers for brushless dc motors - Hayder Yousif Abed; Abdulrahim Thiab Humod; Amjad J. Humaidi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This work presented two fuzzy logic (FL) schemes for speed-controlled brushless DC motors. The first controller is a Type 1 FL controller (T1FLC), whereas the second controller is an interval Type 2 FL controller (IT2FLC). The two proposed controllers were compared in terms of system dynamics and performance. For a fair comparison, the same type and number of membership functions were used for both controllers. The effectiveness of the structures of the two FL controllers was verified through simulation in MATLAB/SIMULINK environment. Simulation result showed that IT2FLC exhibited better performance than T1FLC.